Discussing Instructional Leadership in the Context of Sekolah Penggerak (Transforming Schools) - Raihani, Raihani; Maulana, Tri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This paper discusses the concept of instructional school leadership introduced by the government to schools in Indonesia as part of a larger educational reform since 2019. Although the spirit of employing a type of instructional leadership has been quite strong from the Ministry of Education, Culture, Research and Technology (MOECRT), a solid and thoughtful concept is hardly found. Therefore, this paper uses a training material that was incorporated in the Guru Penggerak training which includes a slide for instructional leadership. We analyse this material in the light of the evolving theories of instructional leadership in the literature, contextual demands and changes occurring surrounding schools. We found that Rutherford’s concept of instructional leadership used in the ‘Guru Penggerak’ training does not seem to be in line with the literature since it is too broadly conceptualised and does not at all touch the very core business of classroom and instruction